How entrepreneurship solves the problem of unemployment in society, and what are its effects on the growth of the economy? : - Mihyar, Sari (2021)
The discovery of Covid-19 has led many countries and governments to take forceful and harsh measures, locking down cities for months. These measures have caused many to lose their jobs and businesses to file for insolvency, raising unemployment rates to percentages that had not been reached in years. This research has discovered the effect start-ups have on the United States, having 99% of its businesses being small and medium enterprises. Furthermore, this study is focused on the relationship between entrepreneurship and its effects on unemployment in the United States of America. This research investigates whether entrepreneurship can be a contributing factor to solving the issue of unemployment and whether it adds to the country's economic growth by performing both regression and descriptive analysis on different variables to determine existing and hidden relationships. The hypotheses proposed in the regression analyses were rejected, which shows no existing relationships between the variables studied. One descriptive analysis showed that the younger the individual, the more time they will spend looking for a job. In contrast, the others showed no relationship without taking into consideration other factors that affect unemployment. Even though the results showed no relationship, unemployment is a broad topic with multiple factors and elements affecting it. Furthermore, unemployment reasons differ between individuals, and for this, qualitative research might be more appropriate. However, this research has proved that there is no relationship between the studied variables, which can be considered for future research.